Results of a Survey Offering Clinical Insights into Speech-Language Pathology Telepractice Methods - Elizabeth U. Grillo (International Journal of Telerehabilitation)
A telepractice survey was administered to the American Speech-Language-Hearing Association Special Interest Group 18 Telepractice affiliates and attendees of the Waldo County General Hospital Speech-Language Pathology Telepractice Training program in Maine, USA over the summer of 2016.   Sixty-seven respondents completed the survey.  The survey explored demographics of clients and clinicians, costs and equipment, learning opportunities, use of the client’s environment and caregivers/e-helpers, and method adaptations in telepractice.  The results of the survey provide information on the current state of telepractice methods in speech-language pathology from experienced practitioners.  This information may be used to develop telepractice models and to prepare speech-language pathology graduate students in the delivery of telepractice methods.